Experimental alteration of the relationshp between the external calcium concentration and the contractile force generated by auricular trabeculae isolated from the heart of the frog, Rana pipiens - Chapman, R. A. (1971)
1. The contractile strength generated by isolated frog auricular trabeculae has been determined by perfusion with high-K Ringer over a range of [Ca](o). 2. Experiments are described in which the cubic relationship between the contracture tension and [Ca](o) has been changed to a square or a linear relationship. 3. These results have been interpreted by proposing that three Ca compounds, whose concentrations are proportional to [Ca](o), act co-operatively at some stage of the process leading to the generation of tension. 4. The change in contractile strength, determined by regular electrically evoked twitches, has been investigated at different temperatures and the results have been explained by assuming that the concentrations of the three hypothetical activating compounds vary at different rates when [Ca](o) is altered. 5. The staircase response is supposed to develop as the consequence of an increase in the concentrations of the two activating Ca compounds with the slowest time constants. 6. The possible physical representations of the hypothetical activating compounds are discussed.